Virtual Platform of Educational Institutionalism in the Context of Social Transformations - Zhukova Galіna; Mordous, Iryna (Studia Warmińskie, 2021)
The article deals with theoretical aspects of educational institutionalism in the context of the issues of virtualization of the educational process, which have been updated as a result of modern social challenges associated with the COVID-19 pandemic. The conclusions formulated by the authors state the existing threats to institutional approaches in education, regarding their shift towards virtualization. Virtual-digital transformation of education forms not only a number of innovative-technical, pedagogical, managerial, economic, and financial but also value changes. The situational socio-educational experience of using virtual platforms has confirmed the need for a systematic study of the virtualization of the educational environment within the framework of the theory of institutionalism and its conceptualization to create alternative approaches to existing technologies for the efficient functioning of the education system.